Microwave-gated dynamic nuclear polarization. Issue 44 (26th October 2016) - Bornet, Aurélien; Pinon, Arthur; Jhajharia, Aditya; Baudin, Mathieu; Ji, Xiao; Emsley, Lyndon; Bodenhausen, Geoffrey; Ardenkjaer-Larsen, Jan Henrik; Jannin, Sami
Abstract : Dissolution dynamic nuclear polarization (D-DNP) efficiency can be significantly boosted by a combination of microwave gating and cross polarization at low temperatures. Abstract : Dissolution dynamic nuclear polarization (D-DNP) has become a method of choice to enhance signals in nuclear magnetic resonance (NMR). Recently, we have proposed to combine cross-polarization (CP) with D-DNP to provide high polarization P ( 13 C) in short build-up times. In this paper, we show that switching microwave irradiation off for a few hundreds of milliseconds prior to CP can significantly boost the efficiency. By implementing microwave gating, 13 C polarizations on sodium [1- 13 C]acetate as high as 64% could be achieved with a polarization build-up time constant as short as 160 s. A polarization of P ( 13 C) = 78% could even be reached for [ 13 C]urea.